2018
DOI: 10.3389/fphar.2018.00382
|View full text |Cite
|
Sign up to set email alerts
|

Extracts From Hypericum hircinum subsp. majus Exert Antifungal Activity Against a Panel of Sensitive and Drug-Resistant Clinical Strains.

Abstract: During the last two decades incidences of fungal infections dramatically increased and the often accompanying failure of available antifungal therapies represents a substantial clinical problem. The urgent need for novel antimycotics called particular attention to the study of natural products. The genus Hypericum includes many species that are used in the traditional medicine to treat pathological states like inflammations and infections caused by fungi. However, despite the diffused use of Hypericum-based pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Although, to the best of our knowledge, previous studies reporting procyanidins in H. triquetifolium and H. neurocalycinum have not been published, catechin and several oligomeric procyanidins (such as A2, B2, and B3) have been identified and isolated from H. perforatum ( Ploss et al, 2001 ; Hellenbrand et al, 2015 ) and H. hircinum subsp. Majus ( Tocci et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although, to the best of our knowledge, previous studies reporting procyanidins in H. triquetifolium and H. neurocalycinum have not been published, catechin and several oligomeric procyanidins (such as A2, B2, and B3) have been identified and isolated from H. perforatum ( Ploss et al, 2001 ; Hellenbrand et al, 2015 ) and H. hircinum subsp. Majus ( Tocci et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity was evaluated on two normal cell lines, namely PBMC and human foreskin fibroblast Hs27 (ATCC ® CRL-1634™, Manassas, VA, USA). PBMCs were obtained from buffy coat of healthy donors (as approved by the ethical committee of the local health center, Azienda Provinciale per i Servizi Sanitari, Provincia Autonoma di Trento) within 4 h from sample collection and isolated as previously described [ 9 ]. Cells were seeded in 96-well culture plates at concentration of 5000 cells/well and incubated for 24 h before treatment with H. mexicanum extracts and isolated compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the outcomes of the available antifungal therapy are not satisfactory, and therefore the discovery of new active compounds is a priority considering this alarming gap in the anti-fungal pipeline [ 7 ]. The search for novel antifungal agents from medicinal plant sources [ 8 , 9 ] offers a promising path to addressing this gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, UPLC-QTOF-MS/MS or GC/MS studies have shown that both SC and PS contains a variety of active components such as phenols, flavonoids, phenylpropenoids and triterpenoids, which exerts anti-oxidant, anti-bacteria, anti-inflammatory and anti-virus effects ( Lee et al, 2012 ; Hwang et al, 2019 ; Yang et al, 2019 ). A large number of experimental data showed that herbal extracts and natural products were effective in preventing and treating several disease such as Non-alcoholic fatty liver disease, fungal infection ( Tocci et al, 2018 ; Zhang et al, 2018b ). However, due to the complexity of the composition of the herbs, the underlying molecular mechanism of this two herbs in treatment of pelvic inflammatory disease is not clear.…”
Section: Introductionmentioning
confidence: 99%